Mixed-integer convex model for VAr expansion planning - Lopez, Julio Cesar [UNESP]; Mantovani, J. R.S. [UNESP]; Sanz, Javier Contreras (Institute of Electrical and Electronics Engineers (IEEE), 2014)
This paper presents a mixed-integer convex-optimization-based approach for optimum investment reactive power sources in transmission systems. Unlike some convex-optimization techniques for the reactive power planning solution, in the proposed approach the taps settings of under-load tap-changing of transformers are modeled as a mixed-integer linear set equations. Are also considered the continuous and discrete variables for the existing and new capacitive and reactive power sources. The problem is solved for three significant demand scenarios (low demand, average demand and peak demand). Numerical results are presented for the CIGRE-32 electric power system.
Keywords: Convex; demand scenarios; mixed-integer; reactive power planning; reactive power sources; taps settings